UPAYA PENCEGAHAN KENAKALAN REMAJA DALAM MENINGKATKAN MUTU PENDIDIKAN DI SEKOLAH MENENGAH ATAS - Istiqomah Nur Ahya; Sri Mariana; Miftahul Fitri; Hila Liani; Oktami Achni; Tri Asthi Wulandari; Devi Saputri; Doni Aprizal Hadi; Wulan Musana Putri; Arya Tri Agustin K (Jurnal Pengabdian Masyarakat Khatulistiwa, 2025)
ABSTRACTJuvenile delinquency is a social issue that requires serious attention from various parties, particularly families, schools, and the community. This community service activity aims to provide$ education and guidance to high school stude$nts to prevent deviant behavior and improve the overall quality of education. The implementation methods included lectures socialization and student development activities emphasizing moral and religious values. The program targeted high school students who are$ vulnerable to negative$ influences such as unhealthy peer interactions, excessive use of social media and aggressive$ behavior. The results of the activity indicate an increase in students understanding of the impacts of juvenile delinquency and an improvement in their attitudes discipline, and learning motivation. The posttest scores showed a significant increase compared to the pretest results demonstrating the e$ffectiveness of the interventions provided. This program is expected to serve as a sustainable preventive e$ffort to develop well-behaved, discipline$d, and high-quality young ge$ne$rations.Keywords: juvenile$ delinquency, prevention, educational quality ABSTRAKKenakalan remaja merupakan salah satu permasalahan sosial yang perlu mendapatkan perhatian serius dari berbagai pihak, terutama keluarga, sekolah, dan masyarakat. Ke$giatan pe$ngabdian ke$pada masyarakat ini bertujuan untuk memberikan edukasi dan pembinaan kepada remaja di Sekolah Menengah Atas agar mampu menghindari perilaku menyimpang serta dapat meningkatkan mutu Pendidikan disekolah. Metode$ pelaksanaan kegiatan dilakukan me$lalui ceramah, sosialisasi, dan pembinaan yang menekankan pada nilai-nilai moral serta agama. Sasaran kegiatan adalah remaja di Sekolah Menengah Atas yang rentan terhadap pengaruh negatif seperti pergaulan bebas, pe$nyalahgunaan media sosial, dan perilaku agresif. Hasil ke$giatan menunjukkan adanya pe$ningkatan pe$mahaman peserta tentang dampak kenakalan remaja serta meningkatnya nilai siswa dalam menunjang mutu pendidikan. Kegiatan ini diharapkan menjadi langkah preventif yang berkelanjutan dalam menciptakan generasi muda yang berakhlak, disiplin, dan bermutu.Kata kunci : kenakalan remaja, pencegahan, mutu pendidikanJuve$nile$ de$linque$ncy is a social issue$ that re$quire$s se$rious atte$ntion from various partie$s, particularly familie$s, schools, and the$ community. This community se$rvice$ activity aims to provide$ e$ducation and guidance$ to high school stude$nts to pre$ve$nt de$viant be$havior and improve$ the$ ove$rall quality of e$ducation. The$ imple$me$ntation me$thods include